The Review of the Most Effective of Online Advertisement Techniques to Affect Online Customer Buying Decision (Global Journal of Management and Business Research, 2014)
Advertisement is one of the common marketing strategy tools which can help to influence customer buying decision and perception towards the particular brand. Thus, online business is getting more and more popular in contemporary times due to the technology advanced which lead to the business market became more competitive now. Marketers use various techniques of online advertisement to get the attention from online customers in order to compete in the market. In this essay will describe the effectiveness of online advertisement techniques and the perception of customer that influence their buying decision.
Keywords: online advertisement; e-commerce; perception of online customers; consumer behavior